Varieties of Knowledge and Skill-Based Pay Design - Milanowski, Anthony (Education Policy Analysis Archives, 2003)
This article describes the design of knowledge and skill-based pay systems for K-12 teachers in six U.S. school districts and one charter school. Based on a theory of action that relates knowledge and skill- based pay systems to improvements in instruction, and the expectancy theory of motivation, seven dimensions for comparison are identified and the systems are compared based on these dimensions. While there were a variety of reasons for designing new pay systems, similarities included that teachers were involved in the design processes, and that the knowledge and skills rewarded are more closely related to instruction than in the traditional salary schedule (though none of the systems placed heavy emphasis on content-specific pedagogy). Most systems made use of existing standards or definitions of good teaching, such as the Framework for Teaching (Danielson, 1996). While most of the systems involved performance-based assessments of teacher skills, in no case were seniority and graduate degrees eliminated as a basis for pay progression. Few of the programs had developed a coordinated professional development program specifically linked to the knowledge and skills rewarded by the new pay system. Implications for policy makers and system designers are drawn.